FRI0313 Prediction of total knee replacement in a 6-month multicentre clinical trial with chondroitin sulfate in knee osteoarthritis: Results from a 4-year observation. (23rd January 2014) - Raynauld, J.-P.; Martel-Pelletier, J.; Dorais, M.; Abram, F.; Haraoui, B.; Choquette, D.; Morin, F.; Bessette, L.; Beaulieu, A.; Pelletier, J.-P.
Abstract : Background: The guidelines from the regulatory agencies require that joint structure modification also translate into a significant clinical benefit for the patient before allowing the claim of DMOAD (1). To this end, the prevention of patient disability and of the need for joint replacement has been suggested as possible clinically relevant outcomes (2). Objectives: To predict from clinical trial and MRI data the incidence of total knee replacement (TKR) during the long-term follow-up of knee osteoarthritis (OA) patients who formerly received chondroitin sulfate (CS) or placebo. Methods: Symptomatic knee OA patients participating in a previous 6-month randomized, double-blind controlled trial evaluating the impact of CS (Condrosan®, Bioibérica S.A., Barcelona, Spain) (800 mg/day) vs. placebo, with subsequent 6-month extension with all patients on CS, were contacted to evaluate retrospectively the incidence of TKR of the study knee. A sub-group of patients (n=51) belonging to the according-to-protocol cohort were selected for this post-hoc retrospective analysis. The TKR incidence was assessed with a standardized phone interview. Results: The patients' mean age was 62.9 years, 61% were female and the average body mass index was 30.6 kg$/$m 2 . A total of 13.7% TKRs were performed upon this sub-population in the time frame of 4 years after patient enrolment. More TKRs were performed within the placebo (71%) than the CS group (29%) (p=0.150, logistic regression). The baseline values of WOMAC pain (p=0.019, logistic regression), stiffness (p=0.013) and function (p=0.044), bone marrow lesions of the medial compartment (p=0.030), and C-reactive protein (CRP) levels (p=0.040) were strong predictors of TKR. Changes at 1 year in the medial cartilage volume (p=0.046) also predicted the occurrence of TKR. Conclusions: In a knee OA clinical trial, it is possible to predict a "hard" outcome such as TKR using information from clinical and MRI data. The results also support the use of MRI as a surrogate for joint tissue damage upon which a DMOAD such as CS may act. References: Guidance for the Industry. Clinical Development Programs for Drugs, Devices and Biological Products Intended for the Treatment Osteoarthritis. US Department of Health and Human Services. Food and Drug Administration, Center for Drug Evaluation and Research, July 1999. Altman RD et al. Osteoarthritis Cartilage 2005;13:13-9. Disclosure of Interest: None Declared